1994
DOI: 10.1095/biolreprod51.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor Receptor in the Preimplantation Uterus and Blastocyst of the Western Spotted Skunk1

Abstract: The western spotted skunk is unique in that its blastocysts undergo a 180-220-day period of arrested development before implantation. We investigated the potential role of epidermal growth factor (EGF)-related growth factors in regulating uterine and embryonic development in this species by studying the status of EGF receptor (EGF-R) in these tissues during delayed implantation and resumption of embryonic development. The cell-specific distribution of EGF binding sites and the expression of EGF-R mRNA were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…It can terminate diapause in ovariectomized rats in the absence of the estrogen pulse (Johnson & Chatterjee 1993), and members of the EGF family of growth factors, including heparin-binding EGF (hbEGF) and amphiregulin are expressed in overlapping patterns by the uterus during rodent implantation (Dey et al 2004). The expression pattern of hbEGF at sites of implantation prior to embryo activation implicates it as a uterine factor effecting termination of diapause in rodents (Das et al 1994). DNA microarray comparison of dormant and activated mouse blastocysts indicates that activation is associated with the expression of the gene encoding hbEGF, as well as the EGF receptor isoforms ErbB1 and ErbB4 (Hamatani et al 2004).…”
Section: Uterine Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can terminate diapause in ovariectomized rats in the absence of the estrogen pulse (Johnson & Chatterjee 1993), and members of the EGF family of growth factors, including heparin-binding EGF (hbEGF) and amphiregulin are expressed in overlapping patterns by the uterus during rodent implantation (Dey et al 2004). The expression pattern of hbEGF at sites of implantation prior to embryo activation implicates it as a uterine factor effecting termination of diapause in rodents (Das et al 1994). DNA microarray comparison of dormant and activated mouse blastocysts indicates that activation is associated with the expression of the gene encoding hbEGF, as well as the EGF receptor isoforms ErbB1 and ErbB4 (Hamatani et al 2004).…”
Section: Uterine Factorsmentioning
confidence: 99%
“…Further, hbEGF expression is induced in the uterus by estrogen (Zhang et al 1998), the proximal signal for the termination of diapause. In addition, EGF receptors are present in dormant carnivore embryos, and their signaling activity is increased associated with escape from diapause (Paria et al 1994). It is therefore reasonable to speculate that estrogen-induced expression of EGF and EGF-like factors from the uterus and embryo, acting on cognate receptors in the blastocyst, reinitiates development.…”
Section: Uterine Factorsmentioning
confidence: 99%
“…The EGF-R has been demonstrated in preimplantation embryos of man and pig (Zhang et al 1992;Chia et al 1995) and in uterus and blastocysts of the western spotted skunk (Paria et al, 1994) and mouse (Paria et al 1993;Tong et al 1996;Brison and Schultz, 1996). Its involvement in early development is shown by the impairment of development in EGF-R knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling proteins inside the cell, such as phospholipase C, then bind to these new phosphorylated tyrosine residues, initiating the signaling cascade that ultimately elicits DNA synthesis and cellular proliferation in a variety of cell types [5,6]. It has been reported that EGF and EGFR are highly expressed in preimplantation embryos, suggesting that EGFR signaling is involved in early embryo development in an autocrine and/or paracrine manner [7,8]. Moreover, Lee and Fukui [9] reported that treatment with EGF increased the total cell number of blastocysts in vitro.…”
Section: Introductionmentioning
confidence: 99%